S100A12 as Biomarker of Disease Severity and Prognosis in Patients With Idiopathic Pulmonary Fibrosis - Li, Yupeng; He, Yaowu; Chen, Shibin; Wang, Qi; Yang, Yi; Shen, Danting; Ma, Jing; Wen, Zhe; Ning, Shangwei; Chen, Hong (Frontiers in Immunology, 2022)
Background: Idiopathic pulmonary fibrosis (IPF) is one of interstitial lung diseases (ILDs) with poor prognosis. S100 calcium binding protein A12 (S100A12) has been reported as a prognostic serum biomarker in the IPF, but its correlation with IPF remains unclear in the lung tissue and bronchoalveolar lavage fluids (BALF). Methods: Datasets were collected from the Gene Expression Omnibus (GEO) database. Person correlation coefficient, Kaplan-Meier analysis, Cox regression analysis, functional enrichment analysis and so on were used. And single cell RNA-sequencing (scRNA-seq) analysis was also used to explore the role of S100A12 and related genes in the IPF. Results: S100A12 was mainly and highly expressed in the monocytes, and its expression was down-regulated in the lung of patients with IPF according to scRNA-seq and the transcriptome analysis. However, S100A12 expression was up-regulated both in blood and BALF of patients with IPF. In addition, 10 genes were found to interact with S100A12 according to protein-protein interaction (PPI) network, and the first four transcription factors (TF) targeted these genes were found according to hTFtarget database. Two most significant co-expression genes of S100A12 were S100A8 and S100A9. The 3 genes were significantly negatively associated with lung function and positively associated with St George's Respiratory Questionnaire (SGRQ) scores in the lung of patients with IPF. And, low expression of the 3 genes was associated with higher mortality in the BALF, and shorter transplant-free survival (TFS) and progression-free survival (PFS) time in the blood. Prognostic predictive value of S100A12 was more superior to S100A8 and S100A9 in patients with IPF, and the composited variable [S100A12 + GAP index (gender, age, and physiological index)] may be a more effective predictive index. Conclusion: These results imply that S100A12 might be an efficient disease severity and prognostic biomarker in patients with IPF.